Animal-selves in Inuit Dream-cultures - Milne, Louise (2024)
Arctic shamanism can be regarded as a specialised dream-culture, providing a framework wherein certain individuals could gain mastery by internalising the collective mythological system and aligning that with their own capacity to dream. The forms of animals are central in this phenomenon. Shamanic activity traditionally focussed on actual hunting processes (location of game, enforcement of ritual and other rules governing the taking of game). They managed this work by communicating with animal spirits (among others). A life-threatening encounter with a charismatic animal predator was a standard path into shamanism. And shamans wielded their power through semi-autonomous animal-avatars — as lovers, companions or servants — contacted through dreams, visions or second-sight.Inuit animal dreams make an interesting case-study, due to the remarkable time-depth of their recorded dreams and visions (late 18C — present). The Inuit, like many tribal peoples, slept and dreamt together. They shared sleeping habits, customs of dream-sharing, beliefs about the relationship between dream-events and everyday life; they evolved a sophisticated taxonomy of dream-types. All this helped sustain the profile and reception of “culture-dreams” involving animals; animal encounters as gateways to initiation, animal-avatars in dreams generally. As their relations with modernity changed, so did their dream-relations with animals.This paper outlines some of these trajectories, drawing on texts and visual materials from different time periods. The situation of animals in Inuit dream-cultures mirrors changes in subsistence and education. Modernisation, externally imposed or internalised, entailed the suppression/rejection of indigenous traditions; followed, in the later 20C, by revaluations and attempts at renewal. Relevant also is the impact of Christian missions; most recently Pentecostalists, whose spirit traditions identify non-human dream-creatures as devils. Key cultural patterns concerning animal-avatars remain, but the experience ...